(untitled) - Lynch, Michael (Sunderland, Mass., 2007)
The availability of genomic blueprints for hundreds of species has led to a transformation in biology, encouraging the proliferation of adaptive arguments for the evolution of genomic features. This text explains why the details matter and presents a framework for how the architectural diversity of eukaryotic genomes and genes came to arise.
Keywords: Evolutionary genetics,Di truyền học tiến hóa